KONTEN KREATIF BAHASA BALI SEBAGAI MEDIA PEMBELAJARAN MASA PANDEMIPERSPEKTIF SEMIOTIKA VISUAL - I Gst Md Swastya Dharma Pradnyan; I Wayan Juliana (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
The effectiveness of online learning has led to various speculations among the public, especially in Bali. One of them is the decline in the quality of the material delivered by teachers to students. However, academics answer parents's concerns through innovative learning media to ensure the existence of education in Bali. In particular in the Balinese language subject, there are several efforts made by academics including Balinese language conservation activists, one of which is the creation of creative content as a medium of learning. Various transformations present the latest innovations in order to reduce the abstraction of students' understanding of Balinese language material which in fact requires special guidance in its delivery.The works that have been uploaded via social media or mobile applications. Contains various interpretations of meaning based on the visual semiotic paradigm. The visualization process is collaborated between regional knowledge and technology so that it represents the cultural values contained in it, including the tradition of the tumpek wariga ceremony, the formation of student characterization through depictions of puppet figures, and moral ethical values in communication.Visual semiotics describes the basic concept of one of the previous semiotics experts, namely Charles Sanders Pierce, by focusing on the typological relation of signs between Iconicity, Index and Symbol, so as to be able to produce a sign production system. In addition, in the process of interpreting the meaning of words contained in the learning media, they are analyzed according to the six language functions of Roman Jakobson.Keywords ; Creative Content, Learning Media, Visual Semiotics.